Reflecting Upon Latin-American Cities from the XVI and XIX Centuries - Camargo, Márcia da Costa Rodrigues de (Sustainability in Debate, 2014)
Fania Fridman (org.). Cidades do Novo Mundo. Rio de Janeiro: Garamond, 2013. 180 p. Bibliografia, Índice. ISBN 9788576172956.